Predicting the Probability of Exceeding Critical System Thresholds - Krammer, P.; Kvassay, M.; Hluchý, L. (Проблеми програмування, 2018)
In this paper we show how regression modelling can be combined with a special kind of data transformation technique that improves model precision and produces several “preliminary” estimates of the target value. These preliminary estimates can be used for interval estimates of the target value as well as for predicting the probability that it has or will exceed arbitrary predefined thresholds. Our approach can be combined with various regression models and applied in many domains that need to estimate the probability of system malfunctions or other hazardous states brought about by system variables exceeding critical safety thresholds. We rigorously derive the formulas for the probability of crossing an upper bound and a lower bound both separately (one-sided intervals) and together (a two-sided interval), and verify the approach experimentally on a real dataset from the electric power industry. У цій статті показано, як регресійне моделювання можна комбінувати зі спеціальним видом перетворення даних, яке покращує точність моделі і дає кілька «попередніх» оцінок цільового значення. Ці попередні оцінки можна використовувати для інтервальних оцінок цільового значення, а також для прогнозування ймовірності того, що воно прийме або перевищить довільні попередньо визначені порогові значення. Наш підхід можна комбінувати з різними регресійними моделями і застосовувати в багатьох областях, які повинні оцінювати вірогідність збоїв системи або інших небезпечних станів, викликаних системними змінними, що перевищують критичні пороги безпеки. Ми строго виводимо формули для ймовірності перетину верхньої та нижньої межі як окремо (односторонні інтервали), так і разом (двосторонній інтервал) і перевіряємо наш підхід експериментально на реальному наборі даних з електроенергетики. В этой статье показано, как регрессионное моделирование можно комбинировать со специальным видом преобразования данных, которое улучшает точность модели и дает несколько «предварительных» оценок целевого значения. Эти предварительные оценки могут использоваться для интервальных оценок целевого значения, а также для прогнозирования вероятности того, что оно примет или превысит произвольные предопределенные пороговые значения. Наш подход можно комбинировать с различными регрессионными моделями и применять во многих областях, которые должны оценивать вероятность сбоев системы или других опасных состояний, вызванных системными переменными, превышающими критические пороги безопасности. Мы строго выводим формулы для вероятности пересечения верхней и нижней границы как отдельно (односторонние интервалы), так и вместе (двухсторонний интервал), и проверяем наш подход экспериментально на реальном наборе данных из электроэнергетики.